FINITE CONTROL SET MODEL PREDICTIVE CONTROL BASED 7-LEVEL TRIPLE BOOST INVERTER FOR 1-Φ GRID CONNECTED APPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
Due to its reliability and great power handling capacity, multi-level inverters (MLIs) have been the preferred option for the majority of industrial applications. This multilevel inverter suggests an innovative 7-level triple boost inverter that can be controlled by the Model Predictive Control (MPC). This design decreases components just by using eight switches, one diode, and two capacitors for 7-level inverter. Two of the eight switches are also used in the path for charging the capacitors. This approach can overcome the limitations of traditional control methods used with MLIs because it is simple to implement. A greater variety of voltages can be obtained by the conventional system. The proposed 7-level MLI is controlled using a Finite Control Model Predictive Control (FCS-MPC). MATLAB/Simulink can be used to model this 7-level structure. The results show that the Control scheme can effectively track the load current as well as the system functions properly.